PENGARUH CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN MIE LEMONILO OLEH GENERSI Z DI ARMY EVENT SOLO - Nuzulul Wakhid, Erna; Djati Purnama, Kusna (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2024)
Instant noodles are one of the fast food items favored by the public due to their delicious taste, convenience, and quick preparation at an economical price. This research aims to examine and determine the influence of brand image, Korean wave, and brand ambassador on the purchasing decisions of Lemonilo's NCT Dream edition noodles. The research method used is quantitative. Data collection in this study is done through observation and questionnaires. The data analysis method employed includes validity testing, reliability testing, and multiple linear regression analysis. Data collection techniques involve primary data in the form of Likert scale questionnaires and secondary data from literature and previous research. Data analysis is performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of the smartPLS application. The research results indicate that brand image, the Korean wave, fan loyalty, and brand ambassadors have a positive and significant impact on consumers' purchasing decisions for NCT Dream Lemonilo noodles.